Estudo de propriedades químicas e físicas de revestimentos de Ni-P, Fe-P E Ni-Fe-P - Soares, Henrique Jorge Mascarenhas (2021)
This work aimed to evaluate the formation of Fe-P, Ni-P and Ni-Fe-P coatings at pH less than 2, as well as their morphologies and behaviors in electrochemical corrosion tests. Fe-P and Ni-P films were formed at 80 mA cm– 2 and Ni-Fe-P films at 60 mA cm– 2 at a temperature of 55 °C with higher percentages of phosphorus and without cracks. The morphology of the coatings, as well as the thicknesses were obtained by scanning electron microscopy (SEM) and the chemical composition of the coatings was analyzed by X-ray dispersive energy (EDX). To evaluate the structure of the films, the X-ray diffraction technique (XRD) was used. Corrosion studies were performed using linear potentiodynamic polarization curves and electrochemical impedance spectroscopy at 25 ± 0.5 °C in 0.1 mol cm– 3 NaCl. The coatings chosen for the electrochemical tests were Fe-P, constituted in mass by 91.1% in Iron, 4.3% in Phosphorus and the remainder in oxygen, Ni-P constituted in mass by 86.8% in Nickel, 9.5% in Phosphorus and the remainder equivalent to Oxygen and substrate and Ni-Fe-P made up of 44.1% Nickel, 37.4% in Iron, 11.9% in Phosphorus and the remainder equivalent to Oxygen and substrate. The Fe-P film showed cracks in its morphology and 25% yield in the growth of the film. The Ni-P and Fe-P coatings showed no cracks, with Ni-P showing 50% yield, while Ni-Fe-P with 18% yield showed the lowest yield, among the three films studied. The formation of a phase containing phosphorus was not evidenced by XRD, but it is present in the structure, amorphizing the material. Fe-P coating showed less noble corrosion potential and less corrosion resistance, whereas Ni-Fe-P coating showed to be the most noble corrosion potential and higher corrosion resistance, among the three films studied.